2020
DOI: 10.3390/ijerph17082649
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Long-Term Care Recipients Receiving Home and Community-Based Services and the Factors That Influence Utilization in Taiwan

Abstract: In response to the irreversible aging trend, the Taiwan government has promoted the Long-Term Care (LTC) policy 1.0 launched in 2007 and the LTC policy 2.0 reform since 2016. This study aimed to explore the utilization of formal home and community-based care under LTC policy 1.0 to add scientific support for the on-going LTC policy 2.0 reform. Methods: By using Andersen and Aday’s behavioral model of healthcare utilization, the long-term care dataset was analyzed from 2013 to 2016. A total of 101,457 care reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
1
17
1
Order By: Relevance
“…Most of the studies (44 studies or 66.7%) were secondary data analyses of existing databases, [ 42 , 44 , 45 , 47 , 50 , 51 , 54 , 57 , 59 63 , 65 , 66 , 68 , 69 , 71 , 72 , 74 76 , 80 , 82 , 83 , 87 , 90 , 93 96 , 100 – 102 ]; of which, ten of these studies used econometric analytic techniques [ 41 , 43 , 56 , 64 , 77 , 84 , 86 , 91 , 97 , 98 ]. Other study designs included nine cross-sectional surveys [ 40 , 48 , 55 , 58 , 79 , 81 , 85 , 103 , 105 ], five longitudinal cohort studies [ 46 , 49 , 70 , 78 , 88 ], four retrospective cohort studies [ 73 , 89 , 99 , 104 ], and one each of a case control [ 53 ], quasi experimental [ 52 ], cluster randomized controlled trial [ 92 ] and quality improvement study [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies (44 studies or 66.7%) were secondary data analyses of existing databases, [ 42 , 44 , 45 , 47 , 50 , 51 , 54 , 57 , 59 63 , 65 , 66 , 68 , 69 , 71 , 72 , 74 76 , 80 , 82 , 83 , 87 , 90 , 93 96 , 100 – 102 ]; of which, ten of these studies used econometric analytic techniques [ 41 , 43 , 56 , 64 , 77 , 84 , 86 , 91 , 97 , 98 ]. Other study designs included nine cross-sectional surveys [ 40 , 48 , 55 , 58 , 79 , 81 , 85 , 103 , 105 ], five longitudinal cohort studies [ 46 , 49 , 70 , 78 , 88 ], four retrospective cohort studies [ 73 , 89 , 99 , 104 ], and one each of a case control [ 53 ], quasi experimental [ 52 ], cluster randomized controlled trial [ 92 ] and quality improvement study [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…For studies supporting higher propensity among women, women had a higher probability of first-time use of any services, were more likely to seek out home care services and higher probability of using support services [ 74 , 93 , 94 ]. Another study suggested that increased home care use can be explained by older age in women recipients and being widowed having married older men.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Community-based care resources could include community care stations, daycare providers, long-term care institutions, and medical institutions that are located in communities and serve the people who live there. Studies using keywords such as "community care", "elderly care", and "geographical accessibility" have focused on the geographical accessibility in healthcare resources, and related analyses highlight the variables of distance, population demand, and number of medical resource suppliers [16,17,20,28,[32][33][34][35][36][37], all of which influence the utilization of home and community-based services among recipients of long-term care in Taiwan [38], as well as the accessibility of institutional healthcare facilities for the elderly [39][40][41]. Study of care resources in non-medical communities focus on the business model of community-based care institutions [42] and the types of services provided to people with disabilities and the elderly [43].…”
Section: Optimization Of Community-based Care Resourcesmentioning
confidence: 99%